Penguatan nilai karakter nasionalisme sebagai wujud menjaga persatuan dan kedaulatan negara pada anggota Muda Brigade Mobil (BRIMOB) - Kurnia, Heri; Devi, Lathifah Sandra (Nur Science Institute, 2025)
This community service was carried out as a strategic effort to instill and strengthen the values of nationalism in young members of the Mobile Brigade (Brimob) Battalion A Regiment II of the Pioneer Forces. Battalion A has a command headquarters (Mako) in Kedaung, Pamulang, South Tangerang. As the front line in maintaining national security and order, young members of the Brimob have a vital role in maintaining the unity and sovereignty of the country. This activity is designed through training, national lectures, group discussions, and simulations of Pancasila values and national insights. The primary purpose of this activity is to foster a sense of love for the homeland, the spirit of defending the country, and awareness of the importance of maintaining the integrity of the Republic of Indonesia. Participants are actively involved in each activity session through a participatory and interactive approach. The results of the service showed a significant increase in the understanding, attitude, and commitment of nationalism among the participants. This activity also encourages the formation of a critical and reflective mindset in facing national challenges in the global era. Hopefully, this program can be a model for sustainable national character development within the police and other security institutions.